The Greenpeace's Efforts for Forest Destruction Management in Riau Province to Achieve National Security - Andi Muhammad Arief Malleleang; I Gede Sumertha KY; Herlina Juni Risma Saragih; Pujo Widodo (CV. AFDIFAL MAJU BERKAH, 2023)
Forests in Indonesia have an essential role in the life of living things for humans, animals and plants. However, deforestation in the context of clearing land for oil palm plantations has threatened the existence of living things that depend on the forest for their lives. Luckily, some people are aware of the destructive impacts caused by deforestation. Some of these people joined non-governmental organizations affiliated with Greenpeace Indonesia. Therefore, the researchers made this study to find out how efforts have been made by Greenpeace, especially in dealing with forest destruction. This study uses qualitative research with data collection methods through interviews and literature studies. Meanwhile, in analyzing the case, they use theories and concepts: The theory of non-governmental organizations, the concept of non-violence, and the concept of national security researchers. The results of this research are the various efforts made by Greenpeace, Greenpeace's efforts in direct action without violence, and Greenpeace's efforts that have been carried out as a manifestation of national security.